Research Status of Diamond-Like Carbon Coatings - Jia, Yongfei (International Journal of Mechanical and Electrical Engineering, 2026)
Diamond-like Carbon (DLC) coatings are amorphous carbon-based thin films composed of randomly mixed sp¹, sp², and sp³ hybridized carbon. They combine the high hardness of diamond and the low friction property of graphite, with performance regulated by the sp³/sp² ratio. Widely used in fields such as mechanical processing, they can address key issues in tool surface modification. This paper reviews its research status: in terms of structure, it includes two core models and two categories (a-C:H, a-C); preparation focuses on PVD (including HiPIMS) and CVD (PE-CVD); aiming at common issues like high internal stress, it summarizes optimization methods such as element doping, which requires balancing stress and hardness. The paper concludes with an outlook on the development trends of preparation technologies and application prospects in tools, providing a reference for industrial optimization.